Digging sticks and agriculture development at the ancient Neolithic site of la Draga (Banyoles, Spain). (April 2020) - López-Bultó, Oriol; Piqué, Raquel; Antolín, Ferran; Barceló, Joan Antón; Palomo, Antoni; Clemente, Ignacio
Highlights: Digging sticks are the most abundant wooden tool at la Draga archaeological site. The digging sticks have been 3D scanned and analysed. Digging sticks were used to till small areas of land. Digging sticks were a basic tool for the early agricultural development. Abstract: Wooden digging sticks are one of the earliest kinds of tool in human evolution, and provably one of the most widely used in prehistory. This paper will focus on its role in the early agriculture development focusing on the case of the digging sticks assemblage of the Early Neolithic waterlogged site of la Draga (Spain). Ethnographically different uses can be attributed to this type of tool, being soil tilling for agricultural proposes the most economically and socially significant. Based on that hypothesis it has been developed an experimental analysis, followed by the use-wear analysis of 3D models, which suggests the use of the digging sticks of la Draga as agricultural tools. This experimental and use-wears new results are combined with the carpological record at la Draga in order to characterise the early agricultural development at the site.